Composite diaphragm compressor membrane, method for producing same, and diaphragm compressor

CN118789906BActive Publication Date: 2026-10-30CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310397316.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-12
Publication Date
2026-10-30
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

专利申请CN 110566444A虽然提供了一种金属膜片表面改性的方法,采用涂覆方式阻止氢进入内部,但是膜片在长期使用过程中,表面涂覆物会脱落导致膜片发生失效几率大大增加

Benefits of technology

[0025]本发明提供的压缩机膜片具有良好的拉伸强度和较大的可变形量,基于该膜片易于设计成大型腔体积流量隔膜压缩机,同时在应用过程中,能够较好的与气缸内壁贴合,从而减少残留气体带来的余隙容积,进而促进压缩机的效率和流量的提高。此外,本发明提供的压缩机膜片,其材质为树脂和碳纤维树脂复合材料,具有良好的抗氢脆和抗腐蚀特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118789906B_ABST
    Figure CN118789906B_ABST
Patent Text Reader

Abstract

The application provides a composite diaphragm compressor diaphragm, a preparation method thereof and a diaphragm compressor. The diaphragm compressor diaphragm has good hydrogen embrittlement resistance, high tensile strength and deformability, can better adhere to the inner wall of a cylinder, thereby reducing the clearance volume caused by residual gas, and is beneficial to improving the efficiency and flow of the compressor. The diaphragm comprises a resin layer, a first composite material layer and a second composite material layer, the first composite material layer and the second composite material layer are respectively laminated on the upper surface and the lower surface of the resin layer, the first composite material layer and the second composite material layer are both carbon fiber resin composite materials, the content of carbon fibers in the carbon fiber resin composite material is more than 90 wt%, the total thickness of the diaphragm is 0.2-0.8 mm, and the thickness of the resin layer is 0.1-0.2 mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of diaphragm compressor technology, and particularly to a composite material diaphragm compressor diaphragm, its preparation method, and a diaphragm compressor. Background Technology

[0002] Diaphragm compressors are positive displacement compressors that compress and transport gas by the reciprocating motion of a diaphragm within a cylinder. The diaphragm is clamped by two limiting plates along its periphery, forming a cylinder. The diaphragm is mechanically or hydraulically driven to reciprocate within the cylinder, thus compressing and transporting the gas. A typical diaphragm compressor consists of a hydraulic system and a gas compression system, separated by a set of metal diaphragms. Existing diaphragm compressors have a three-layer diaphragm structure: two outer diaphragms act as barrier layers, and the middle diaphragm provides a venting path through a fixed O-ring seal; simultaneously dividing the cylinder into a hydraulic oil chamber and a working gas chamber.

[0003] In existing technologies, thin steel plates such as high-carbon steel are suitable materials for making diaphragms, while stainless steel such as 316L and 00Cr15Ni5 is used for corrosive gases. Typically, the thickness of steel diaphragms is between 0.3-0.5 mm. Excessively thick diaphragms will increase their normal stress. To increase the reliability of diaphragm operation, multi-layer diaphragms can be used. During installation, the surfaces of the layers should be coated with oil to reduce interlayer wear caused by friction. In a three-layer diaphragm structure, a narrow groove can be cut into the middle diaphragm. If either the oil-side or gas-side diaphragm ruptures, oil or gas will leak out, which can be detected through a gas sealing groove or pressure sensor.

[0004] For hydrogen diaphragm compressors, the gas-side diaphragm, which comes into contact with hydrogen, is constantly exposed to a high-pressure hydrogen environment. This often leads to hydrogen embrittlement failure due to hydrogen permeation and accumulation within the diaphragm. Current technologies often employ coatings on the diaphragm surface to prevent hydrogen from entering the diaphragm. However, whether the coating is inorganic (e.g., ceramic) or organic (e.g., polytetrafluoroethylene), it tends to detach over long-term use due to poor compatibility with the base metal material, as the diaphragm impacts and collides with the cylinder head wall during each operation.

[0005] The article "Research on Contact Mechanical Behavior of Metal Diaphragm Components in Diaphragm Compressors" points out that insufficient maximum tensile stress in the slip zone of the metal diaphragm is the main cause of its failure. Similarly, the article "Theoretical Analysis of Diaphragm Rupture in Original Diaphragm Design" also indicates that insufficient radial stress of the diaphragm is a major cause of gas rupture. While patent application CN 110566444A provides a method for surface modification of metal diaphragms, using coating to prevent hydrogen from entering the interior, the surface coating will peel off during long-term use, significantly increasing the probability of diaphragm failure. The article "On the influence of heat treatment on microstructure and mechanical behavior of laser powder bedfused Inconel 718" describes the effects of different treatment temperatures and holding times on the grain size and mechanical properties of the material, but does not explain how to obtain hydrogen-resistant metal materials through surface treatment. Summary of the Invention

[0006] This invention aims to provide a composite material diaphragm compressor diaphragm and its preparation method, as well as a diaphragm compressor based on the composite material diaphragm compressor diaphragm of this invention. The compressor diaphragm provided by this invention has high tensile strength and deformability, which can better fit with the inner wall of the cylinder, thereby reducing the clearance volume caused by residual gas and improving the efficiency and flow rate of the compressor.

[0007] To achieve its objective, the present invention provides the following technical solution:

[0008] The first aspect of the present invention provides a composite material diaphragm compressor diaphragm, the diaphragm comprising a resin layer, a first composite material layer and a second composite material layer, wherein the first composite material layer and the second composite material layer are respectively stacked on the upper surface and the lower surface of the resin layer;

[0009] Both the first composite material layer and the second composite material layer are carbon fiber resin composite materials; and the carbon fiber content in the carbon fiber resin composite material is above 90 wt%.

[0010] The total thickness of the diaphragm is 0.2-0.8 mm, and the thickness of the resin layer is 0.1-0.2 mm. The thicknesses of the first composite material layer and the second composite material layer are ≥0.1 mm, preferably 0.1-0.35 mm.

[0011] In a preferred embodiment, the carbon fiber content in the fiber-resin composite material is 90-95%.

[0012] In some embodiments, the resin in the carbon fiber resin composite material and the resin in the resin layer are selected from one or more of PVDF, PTFE, Nylon, and PEEK, preferably from PVDF and / or PTFE.

[0013] In some embodiments, the carbon fiber is selected from one or more of T300, T500, and T700.

[0014] In a preferred embodiment, the first composite material layer and the second composite material layer are made of the same material and have the same thickness.

[0015] In this invention, the first composite material layer, the resin layer, and the second composite material layer are integrally formed into the membrane by hot pressing.

[0016] A second aspect of the present invention also provides a diaphragm compressor, wherein the diaphragm in the diaphragm compressor is the diaphragm described above.

[0017] Preferably, the inner surface of the cylinder of the diaphragm compressor is covered with a resin coating, and more preferably the thickness of the resin coating is less than or equal to 0.1 mm, and more preferably 0.05-0.1 mm.

[0018] More preferably, the resin material used for the resin coating is selected from one or more of PVDF, PTFE, Nylon, and PEEK, and is preferably selected from PVDF and / or PTFE.

[0019] A third aspect of the present invention also provides a method for preparing the composite material diaphragm compressor diaphragm described above, comprising the following steps:

[0020] The first composite material layer, the resin layer, and the second composite material layer are sequentially stacked in a hot press mold, and the film is obtained by hot pressing and cooling.

[0021] In some embodiments, the preparation of the carbon fiber resin composite material required for the first composite layer or the second composite layer specifically includes the following steps:

[0022] Carbon fiber material is impregnated in a resin solution to obtain carbon fiber preimpregnated material, and the carbon fiber preimpregnated material is cured to obtain the carbon fiber resin composite material; preferably, the curing temperature is 50-120℃ and the curing time is 6-12h.

[0023] In a preferred embodiment, the hot pressing conditions include: a pressure of 10-45 MPa, a heating rate of 1-5 °C / min, heating to 250-380 °C and holding at that temperature for 30-120 min.

[0024] The technical solution provided by this invention has the following beneficial effects:

[0025] The compressor diaphragm provided by this invention possesses excellent tensile strength and a large deformability. Based on this diaphragm, it is easily designed into a large-cavity volumetric flow diaphragm compressor. Furthermore, during application, it can fit well against the cylinder inner wall, thereby reducing the clearance volume caused by residual gas and thus promoting the improvement of compressor efficiency and flow rate. In addition, the compressor diaphragm provided by this invention is made of a resin and carbon fiber resin composite material, exhibiting excellent resistance to hydrogen embrittlement and corrosion. Attached Figure Description

[0026] Figure 1 The diagram shown is a schematic diagram of the structure of a diaphragm provided in one embodiment;

[0027] Figure 2 The diagram shown is a partial structural schematic of the inner surface of the cylinder in one embodiment. Detailed Implementation

[0028] To facilitate understanding of the present invention, the following description, in conjunction with embodiments, will further illustrate the invention. It should be understood that the following embodiments are merely for a better understanding of the invention and do not imply that the invention is limited to these embodiments.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The term "and / or" may be used herein to include any and all combinations of one or more of the associated listed items.

[0030] The directional terms such as up, down, left, right, front, back, front, back, top, and bottom mentioned or possibly used in this specification are defined relative to the construction shown in the accompanying drawings. They are relative concepts and may therefore vary depending on their location and usage. The terms "inner" and "outer" refer to directions toward or away from the geometric center of a specific component, respectively.

[0031] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in this technical field can be followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0032] This invention provides a composite material diaphragm compressor diaphragm, see [link / reference]. Figure 1The membrane mainly comprises a resin layer 3, a first composite material layer 1, and a second composite material layer 2, wherein the first composite material layer 1 and the second composite material layer 2 are respectively stacked on the upper and lower surfaces of the resin layer 3, and the three are bonded together to form an integral membrane. Both the first composite material layer 1 and the second composite material layer 2 are carbon fiber resin composite materials; and the carbon fiber content in the carbon fiber resin composite material is above 90 wt%. The total thickness of the membrane is 0.2-0.8 mm, the thickness of the resin layer is 0.1-0.2 mm, and the thicknesses of the first and second composite material layers are ≥0.1 mm, preferably 0.1-0.35 mm. The diaphragm of this invention is an integral structure of carbon fiber resin composite layer-resin layer-carbon fiber resin composite layer, with the carbon fiber content in the composite layer controlled to be above 90wt%, the resin layer thickness controlled to be 0.1-0.2mm, the thickness of the first composite layer and the second composite layer ≥0.1mm respectively, and the total thickness of the diaphragm controlled to be 0.2-0.8mm. The provided diaphragm has good comprehensive performance, not only resisting hydrogen embrittlement, but also having high tensile strength (above 400MPa) and large deformability (above 70%). During application, it can fit well with the inner wall of the cylinder, thereby reducing the clearance volume caused by residual gas, which in turn helps to improve the efficiency and flow rate of the compressor.

[0033] In some preferred embodiments, the carbon fiber content in the carbon fiber resin composite material is controlled at 90-95%, which can take into account high tensile strength and facilitate the complete impregnation and coating of carbon fibers with resin, avoiding the existence of voids. This is conducive to further improving the overall performance of the membrane, and can achieve higher deformation while ensuring tensile strength of over 400 MPa. It is also conducive to further reducing the proportion of residual solvent.

[0034] In this invention, the resin in the carbon fiber resin composite material and the resin in the resin layer are selected from one or more of PVDF, PTFE, Nylon, and PEEK, preferably PVDF and / or PTFE. By using the preferred resin material, the diaphragm and cylinder have less friction, which is beneficial to further improve the diaphragm life and improve the performance of the compressor.

[0035] In some embodiments, the carbon fiber material is selected from one or more of T300, T500, and T700.

[0036] In some preferred embodiments, the first composite material layer 1 and the second composite material layer 2 are made of the same material and have the same thickness. The same first composite material and second composite material are used on both sides of the resin layer of the membrane, so that the membrane has consistent physical properties on the oil side and the gas side. This helps to ensure that the entire membrane has the same coefficient of thermal expansion and prevents the membrane from delaminating due to temperature.

[0037] More preferably, the first composite material layer 1, the resin layer 3, and the second composite material layer 2 are integrally formed into the diaphragm by hot pressing, and the three are tightly and firmly bonded together, resulting in a diaphragm with better stability and longer lifespan.

[0038] This invention also provides a diaphragm compressor, which has a structure basically the same as existing diaphragm compressors, and the similarities will not be repeated here; the main difference lies in the improvement of the diaphragm. The diaphragm in the diaphragm compressor of this invention uses the diaphragm described above, as specifically described above, and will not be repeated here. Preferably, see... Figure 2 A resin coating 5 is formed on the inner surface of the cylinder wall 4 of the diaphragm compressor. Preferably, the thickness of the resin coating 5 is less than or equal to 0.1 mm, more preferably 0.05-0.1 mm. By applying the resin coating, the loss caused by the diaphragm hitting the inner wall of the cylinder can be reduced. At the same time, the deformable surface can make the diaphragm and the inner wall of the cylinder fit better, which is conducive to further reducing the clearance volume caused by residual gas and improving the efficiency and flow of the compressor. It is preferable to control the thickness of the resin coating 5 to 0.05-0.1 mm. This will prevent the diaphragm from deforming too much when it comes into contact with the inner wall of the cylinder due to excessive thickness, which would increase the clearance volume. It will also prevent the thickness from being too thin, which would prevent it from effectively providing buffer protection. The inventors have found that if the resin coating thickness is too large (e.g., greater than 0.1 mm), the diaphragm and the cylinder are prone to slapping during operation, and the resin coating is easy to fall off. Based on the diaphragm of the present invention and the diaphragm compressor with a resin coating of a specific thickness on the inner wall of the cylinder, it has good comprehensive performance, can obtain good diaphragm tensile strength and maximum deformation, and has a relatively low clearance volume ratio. At the same time, the resin coating has good firmness and is not prone to cylinder knocking.

[0039] In a preferred embodiment, the inventors have discovered that the diaphragm compressor based on the composite material layer + resin layer + composite material layer diaphragm of the present invention and the diaphragm compressor with a resin coating on the inner wall of the cylinder, wherein the carbon fiber content of the composite material layer in the diaphragm is controlled at 90-95%, the total thickness of the diaphragm is controlled at 0.2-0.8 mm, the thickness of the resin layer is controlled at 0.1-0.2 mm, the thickness of the first composite material layer and the second composite material layer are respectively controlled at ≥0.1 (preferably 0.1-0.35 mm), and the thickness of the resin coating on the inner surface of the cylinder is controlled at less than 0.1 mm (preferably 0.05-0.1 mm), the diaphragm compressor having the above combination of features has better overall performance, can take into account a diaphragm tensile strength of more than 400 MPa, a maximum diaphragm deformation of more than 75%, and a clearance volume ratio of less than 2%; moreover, during application, there will be no cylinder knocking phenomenon between the diaphragm and the cylinder head, and the resin coating has good firmness and is not easy to fall off.

[0040] More preferably, the resin material used for the resin coating 5 on the cylinder inner wall of the present invention is selected from one or more of PVDF, PTFE, Nylon, and PEEK, preferably selected from PVDF and / or PTFE. Using the preferred resin material not only has a strong bonding force with the cylinder inner wall, but also provides good protection when the diaphragm impacts the cylinder inner wall, reducing wear, and can adhere more tightly to the diaphragm.

[0041] In some preferred embodiments, the resin coating 5 on the cylinder inner wall can be formed by the following steps: 1) cleaning the inner surface of the cylinder to remove surface dirt, for example, by treating the inner surface of the cylinder with a conventional degreaser, and then drying it in a drying oven for, for example, 1-2 hours at a drying temperature of, for example, 100°C; 2) spraying the resin solution onto the inner surface of the cylinder, controlling the amount of spraying according to the required thickness, and then placing it in a drying oven for plasticization, preferably at a temperature of 250-380°C, for a holding time of, for example, 60 minutes. Using these preferred steps and conditions to form the resin coating on the cylinder inner wall allows for more complete plasticization of the resin material and results in a more uniform and robust resin coating.

[0042] Another aspect of the present invention provides a method for preparing the composite material diaphragm compressor diaphragm described above, comprising the following steps: stacking a first composite material layer, a resin layer, and a second composite material layer sequentially in a hot press mold, and obtaining the diaphragm by hot pressing and cooling.

[0043] More specifically, the preparation of the carbon fiber resin composite material required for the first composite layer or the second composite layer includes the following steps:

[0044] Carbon fiber material is impregnated in a resin solution to obtain a carbon fiber preimpregnated material, which is then cured to obtain the carbon fiber resin composite material. Preferably, the curing temperature is 50-120°C in an oven, and the curing time is 6-12 hours. The resin solution is, for example, a 50-60 wt% resin solution, and the impregnation time is, for example, 10-60 minutes, to ensure that the carbon fiber surface is fully wetted. The carbon fiber material is, for example, woven carbon fiber felt.

[0045] In some preferred embodiments, the hot-pressing conditions include: a pressure of 10-45 MPa, a heating rate of 1-5 °C / min, heating to 250-380 °C and holding at that temperature for 30-120 min. The hot pressing can be performed in a hot press. After hot pressing, the material is cooled to room temperature, and then cooled under pressure at a rate of 1-5 °C / min. These preferred hot-pressing conditions facilitate complete impregnation of the resin and carbon fibers and reduce voids, thereby improving properties such as the tensile strength of the membrane.

[0046] The compressor diaphragm provided by this invention has high tensile strength (e.g., reaching 400-800 MPa) and a large deformability (e.g., exceeding 70%, even 80%), and is resistant to hydrogen embrittlement (does not experience hydrogen embrittlement failure). This not only facilitates the design of large-volume, high-flow-rate diaphragm compressors, but also allows for better adhesion to the inner wall during application, reducing clearance volume caused by residual gas and improving compressor efficiency and flow rate. However, traditional metal diaphragms often use 301 stainless steel as the diaphragm material, which balances high tensile strength and high deformability (usually not exceeding 30%), but is prone to hydrogen embrittlement failure during prolonged use in hydrogen gas.

[0047] The present invention will be further illustrated by the following examples.

[0048] Test method description:

[0049] Tensile strength of diaphragms: ASTM D3039 Test method for tensile properties of polymer-based composite materials;

[0050] Maximum deformation of the diaphragm: ASTM D 7264 Standard Method for Testing the Flexural Properties of Resin-Based Composite Materials;

[0051] The proportion of clearance volume to air cavity is determined using a calculation method well-known in the art. Specifically, the proportion of clearance volume to air cavity (%) = (1-V m / V)100%

[0052] Where V is the volume enclosed by the original plane of the diaphragm and the curved surface of the cylinder head on the air side;

[0053] Vm is the volume enclosed by the diaphragm at the point of maximum deformation and the original plane of the diaphragm.

[0054] Example 1:

[0055] 1. Preparation of composite carbon fiber membranes:

[0056] (1) Pre-impregnation:

[0057] The woven T500 carbon fiber felt was impregnated in a 50wt% PTFE resin matrix aqueous dispersion for 30 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0058] (2) Hot pressing

[0059] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.5 mm) and hot-pressed by a hot press machine. The hot press machine pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.5 mm, of which the thickness of the resin layer is 0.2 mm, and the thickness of the composite material layer on the upper and lower surfaces of the resin layer is 0.15 mm.

[0060] 2. Resin spraying on the inner surface of the cylinder:

[0061] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0062] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0063] (2) Surface spraying:

[0064] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.1mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0065] Example 2:

[0066] 1. Preparation of composite carbon fiber membranes:

[0067] (1) Pre-impregnation:

[0068] The woven T500 carbon fiber felt was impregnated in a 60wt% PVDF resin matrix aqueous dispersion for 60 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0069] (2) Hot pressing

[0070] The composite material obtained in step (1) and the PVDF resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PVDF resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.4 mm) and hot-pressed by a hot press. The hot press pressure is 45 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 250℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.4 mm, of which the thickness of the resin layer is 0.2 mm, and the thickness of the composite material layers on the upper and lower surfaces of the resin layer is 0.1 mm.

[0071] 2. Resin spraying on the inner surface of the cylinder:

[0072] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0073] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0074] (2) Surface spraying:

[0075] The inner surface of the cylinder is coated with a 60wt% PVDF resin matrix solution. The spray gun is kept within 20cm of the inner surface of the cylinder, and the coating thickness is 0.08mm. After the predetermined coating thickness is reached, the cylinder is placed in a drying oven for plasticization at a temperature of 250℃ for 1 hour.

[0076] Example 3

[0077] 1. Preparation of composite carbon fiber membranes:

[0078] (1) Pre-impregnation:

[0079] The woven T500 carbon fiber felt was impregnated in a 50wt% PTFE resin matrix aqueous dispersion for 10 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 8 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0080] (2) Hot pressing

[0081] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.5 mm) and hot-pressed by a hot press machine. The hot press machine pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.6 mm, of which the thickness of the resin layer is 0.2 mm, and the thickness of the composite material layers on the upper and lower surfaces of the resin layer is 0.2 mm.

[0082] 2. Resin spraying on the inner surface of the cylinder:

[0083] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0084] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0085] (2) Surface spraying:

[0086] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.1mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0087] Example 4

[0088] 1. Preparation of composite carbon fiber membranes:

[0089] (1) Pre-impregnation:

[0090] The woven T500 carbon fiber felt was impregnated in a 50wt% PTFE resin matrix aqueous dispersion for 5 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 12 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0091] (2) Hot pressing

[0092] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.3 mm) and hot-pressed by a hot press machine. The hot press machine pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.3 mm, of which the thickness of the resin layer is 0.1 mm, and the thickness of the composite material layers on the upper and lower surfaces of the resin layer is 0.1 mm.

[0093] 2. Resin spraying on the inner surface of the cylinder:

[0094] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0095] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0096] (2) Surface spraying:

[0097] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.1mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0098] Comparative Example 1:

[0099] 1. Preparation of composite carbon fiber membranes:

[0100] (1) Pre-impregnation:

[0101] The woven T500 carbon fiber felt was impregnated in a 10wt% PVDF resin matrix aqueous dispersion for 60 min to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 h; the cured carbon fiber impregnated tape was obtained, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0102] (2) Hot pressing:

[0103] The composite material and resin matrix obtained in step (1) are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PVDF resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the inner cavity of the mold is 2 mm) and hot-pressed by a hot press. The hot press pressure is 45 MPa, the temperature rise rate is 5℃ / min, the maximum hot press temperature is 250℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 2 mm, of which the thickness of the resin layer is 1.5 mm, and the thickness of the composite material layer on the upper and lower surfaces of the resin layer is 0.25 mm.

[0104] 2. Resin spraying on the inner surface of the cylinder:

[0105] (1) Cleaning of dirt on the inner metal surface of the cylinder

[0106] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0107] (2) Surface spraying:

[0108] The inner surface of the cylinder is coated with a 10wt% PVDF resin matrix solution. The spray gun is kept within 20cm of the inner surface of the cylinder, and the coating thickness is 0.3mm. After the predetermined coating thickness is reached, the cylinder is placed in a drying oven for plasticization at a temperature of 250℃ for 1 hour.

[0109] Comparative Example 2

[0110] 1. Preparation of composite carbon fiber membranes:

[0111] (1) Pre-impregnation:

[0112] The woven T500 carbon fiber felt was impregnated in a 30wt% PTFE resin matrix aqueous dispersion for 30 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0113] (2) Hot pressing

[0114] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.5 mm) and hot-pressed by a hot press machine. The hot press machine pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.5 mm, of which the thickness of the resin layer is 0.2 mm, and the thickness of the composite material layer on the upper and lower surfaces of the resin layer is 0.15 mm.

[0115] 2. Resin spraying on the inner surface of the cylinder:

[0116] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0117] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0118] (2) Surface spraying:

[0119] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.1mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0120] Comparative Example 3

[0121] 1. Preparation of composite carbon fiber membranes:

[0122] (1) Pre-impregnation:

[0123] The woven T500 carbon fiber felt was impregnated in a 50wt% PTFE resin matrix aqueous dispersion for 30 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0124] (2) Hot pressing

[0125] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.5 mm) and hot-pressed by a hot press. The hot press pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.5 mm, of which the thickness of the resin layer is 0.3 mm, and the thickness of the composite material layers on the upper and lower surfaces of the resin layer is 0.1 mm.

[0126] 2. Resin spraying on the inner surface of the cylinder:

[0127] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0128] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0129] (2) Surface spraying:

[0130] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.1mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0131] Comparative Example 4

[0132] 1. Preparation of composite carbon fiber membranes:

[0133] (1) Pre-impregnation:

[0134] The woven T500 carbon fiber felt was impregnated in a 50wt% PTFE resin matrix aqueous dispersion for 30 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0135] (2) Hot pressing

[0136] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.5 mm) and hot-pressed by a hot press machine. The hot press machine pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.27 mm, of which the thickness of the resin layer is 0.07 mm, and the thickness of the composite material layers on the upper and lower surfaces of the resin layer is 0.1 mm.

[0137] 2. Resin spraying on the inner surface of the cylinder:

[0138] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0139] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0140] (2) Surface spraying:

[0141] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.1mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0142] Comparative Example 5

[0143] 1. Preparation of composite carbon fiber membranes:

[0144] (1) Pre-impregnation:

[0145] The woven T500 carbon fiber felt was impregnated in a 50wt% PTFE resin matrix aqueous dispersion for 30 minutes to ensure that the carbon fiber surface was fully wetted; then cured in an oven at 120℃ for 6 hours to obtain the cured carbon fiber impregnated tape, which is the composite material. The carbon fiber content of the composite material is shown in Table 1.

[0146] (2) Hot pressing

[0147] The composite material obtained in step (1) and the PTFE resin matrix sheet are stacked into three layers, with the top and bottom layers being the composite material obtained in step (1) and the middle layer being the PTFE resin matrix. After stacking, the layers are placed in a square hot press mold (the thickness of the mold cavity is 0.5 mm) and hot-pressed by a hot press. The hot press pressure is 30 MPa, the heating rate is 5℃ / min, the maximum hot pressing temperature is 380℃, and the maximum temperature holding time is 120 min. After holding, the temperature is reduced to room temperature at a rate of 5℃ / min under pressure to obtain a film. The total thickness of the film is 0.5 mm, of which the thickness of the resin layer is 0.3 mm, and the thickness of the composite material layers on the upper and lower surfaces of the resin layer is 0.1 mm.

[0148] 2. Resin spraying on the inner surface of the cylinder:

[0149] (1) Cleaning of dirt on the metal inner surface of the cylinder

[0150] The metal inner surface of the cylinder was treated with a commercially available degreaser, and then placed in a drying oven to dry for 2 hours at a temperature of 100°C.

[0151] (2) Surface spraying:

[0152] A 50wt% PTFE resin matrix solution was used to spray the inner surface of the cylinder. The spray gun was kept within 20cm of the inner surface of the cylinder, and the spray thickness was 0.2mm. After the predetermined spray thickness was achieved, the cylinder was placed in a drying oven for plasticization at a temperature of 380℃ for 1 hour.

[0153] Table 1

[0154]

[0155]

[0156] Compared to Example 1, Comparative Example 5 increased the resin coating thickness to 0.2 mm. Although it exhibited higher diaphragm tensile strength, larger maximum diaphragm deformation, and lower clearance solvent-to-gas-cavity ratio, during testing, a cylinder-slapping phenomenon was observed between the diaphragm and cylinder in the diaphragm compressor based on Comparative Example 5, and the resin coating detached after 1000 tests. However, in Examples 1-4, under the same testing method, neither cylinder-slapping nor resin coating detachment occurred.

[0157] All of the above Examples 1-4 simultaneously satisfy the following conditions: the carbon fiber content in the composite material is above 90wt%, the total thickness of the diaphragm is 0.2-0.8mm, the thickness of the resin layer is 0.1-0.2mm, the thickness of the first composite material layer and the second composite material layer are ≥0.1mm respectively, and the thickness of the resin coating is less than or equal to 0.1mm; the diaphragms of Examples 1-4 can take into account a tensile strength of over 400MPa and a maximum deformation of over 70%, while also taking into account a relatively low clearance volume ratio; at the same time, they are not prone to cylinder slapping during application, and the resin coating is not easy to fall off.

[0158] In the preferred embodiments 1 and 3, compared with embodiments 2 and 4, the carbon fiber content in the composite material was further controlled at 90-95 wt%, resulting in better overall performance. It not only takes into account tensile strength of more than 400 MPa and maximum deformation of more than 75%, but also takes into account a lower clearance volume ratio of less than 2%.

[0159] It is readily understood that the above embodiments are merely illustrative examples for clear explanation and do not imply that the invention is limited thereto. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A diaphragm compressor, characterized in that, The diaphragm compressor diaphragm is a composite material diaphragm compressor diaphragm, which includes a resin layer, a first composite material layer and a second composite material layer, with the first composite material layer and the second composite material layer respectively stacked on the upper and lower surfaces of the resin layer. Both the first composite material layer and the second composite material layer are carbon fiber resin composite materials; Furthermore, the carbon fiber content in the carbon fiber resin composite material is 90-98 wt%; The total thickness of the diaphragm is 0.2-0.8 mm, and the thickness of the resin layer is 0.1-0.2 mm, with the thicknesses of the first composite material layer and the second composite material layer being ≥0.1 mm respectively; A resin coating is formed on the inner metal surface of the cylinder of the diaphragm compressor, and the thickness of the resin coating is 0.05-0.1 mm. The resin material used for the resin coating is selected from one or more of PVDF, PTFE, Nylon, and PEEK; The resin in the carbon fiber resin composite material and the resin in the resin layer are respectively selected from one or more of PVDF, PTFE, Nylon, and PEEK.

2. The diaphragm compressor according to claim 1, characterized in that, The thicknesses of the first composite material layer and the second composite material layer are 0.1-0.35 mm, respectively.

3. The diaphragm compressor according to claim 1, characterized in that, The carbon fiber content in the carbon fiber resin composite material is 90-95%.

4. The diaphragm compressor according to claim 1, characterized in that, The resin in the carbon fiber resin composite material and the resin in the resin layer are respectively selected from PVDF and / or PTFE.

5. The diaphragm compressor according to any one of claims 1-4, characterized in that, The carbon fiber is selected from one or more of T300, T500, and T700.

6. The diaphragm compressor according to any one of claims 1-4, characterized in that, The first composite material layer and the second composite material layer are made of the same material and have the same thickness.

7. The diaphragm compressor according to any one of claims 1-4, characterized in that, The first composite material layer, the resin layer, and the second composite material layer are integrally formed into the diaphragm by hot pressing.

8. The diaphragm compressor according to any one of claims 1-4, characterized in that, The resin material used for the resin coating is selected from PVDF and / or PTFE.

9. The diaphragm compressor according to any one of claims 1-4, characterized in that, The method for preparing the composite material diaphragm compressor diaphragm includes the following steps: The first composite material layer, the resin layer, and the second composite material layer are sequentially stacked in a hot press mold, and the film is obtained by hot pressing and cooling.

10. The diaphragm compressor according to claim 9, characterized in that, The preparation of the carbon fiber resin composite material required for the first composite material layer or the second composite material layer specifically includes the following steps: Carbon fiber material is impregnated in a resin solution to obtain carbon fiber preimpregnated material, and the carbon fiber preimpregnated material is cured to obtain the carbon fiber resin composite material.

11. The diaphragm compressor according to claim 10, characterized in that, The curing temperature is 50-120℃, and the curing time is 6-12 h.

12. The diaphragm compressor according to claim 9, characterized in that, The hot pressing conditions include: a pressure of 10-45 MPa, a heating rate of 1-5 ℃ / min, heating to 250-380℃ and holding at that temperature for 30-120 min.

Citation Information

Patent Citations

  • Diaphragm for diaphragm compressor and method of prolonging service life of diaphragm

    CN110566444A

  • Layered substrate and method for manufacturing same

    CN109715385A

  • Laminate, three-dimensional molded laminate, and method for producing three-dimensional molded laminate

    CN113613876A

  • Cylinder cover of refrigerator compressor

    CN212803529U